Perancangan Film Animasi 3 Dimensi Berjudul “Jangan Menyerah” dengan Metode Pose to Pose - Antasena, Aria; Bustomi, Tommy; Metandi, Farindika (Jurnal Teknik Indonesia, 2022)
3D animation film is a development of 2D animation which is developed through computer technology which is growing rapidly. However, in using computer technology to design a 3D animated film that is still very rigid, it can affect the performance of the animation because the animation does not look real like humans and objects. The purpose of this study is to explain the design of animating an animated film using the method that has been made, namely pose to pose for each pose used based on the animation design that has been made for the film entitled "Jangan Menyerah". Method: This study uses the Multimedia Development Life Cycle (MDLC) method with six stages, namely concept, design, material collection, manufacture, testing, and finally distribution. The concept of the title of the film is not to give up on moral and short film formats. The characters used use the pose to pose method with keypose movements, extreme movements and in between movements. After that, testing and distribution is the final process in making works that are published through social networks. Conclusion Making an animated film designing a 3-dimensional animated film entitled "don't give up" using the pose to pose method, the journey of a child who wants to achieve his goals, can be achieved by following the multimedia development life cycle stage with the last process being distribution on SNS such as YouTube and Instagram